Nitrogen, sulfur, chlorine containing pollutants releasing characteristics during pyrolysis and combustion of oily sludge. (1st August 2020) - Chen, Guanyi; Li, Jiantao; Li, Kai; Lin, Fawei; Tian, Wangyang; Che, Lei; Yan, Beibei; Ma, Wenchao; Song, Yingjin
Graphic abstract: Highlights: Oily sludge releases multiple N/S/Cl pollutants during pyrolysis and combustion. Database and releasing route of N/S/Cl pollutants were established. Organic N/S/Cl functionalities in oily sludge contribute to majority of pollutants. Combustion promotes destruction of organic fractions releasing at low temperature. Abstract: Pyrolysis and combustion have become effective technologies for oily sludge treatment. This paper firstly investigated N/S/Cl pollutants during pyrolysis and combustion of oily sludge in detail by thermogravimetry-mass spectrum (TG-MS) and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). Combined with the distribution characteristics and contents of hazardous elements, the releasing routes were proposed. Three typical decomposition steps were observed: volatilization of water and little hydrocarbons below 200 °C, cracking of hydrocarbons approximately at 200–500 °C, transformation of inorganic compositions at the higher temperature. Double-direction transfer diffusion reaction model was employed with estimated apparent activation energy Ea of 41.97–66.59 kJ·mol −1 for pyrolysis and 52.02–62.42 kJ·mol −1 for combustion. The main pyrolytic products were alkanes and alkenes ranging from C9 to C21, which had the potential to be reused as diesel fuels. Slight amounts of S/Cl-containing species were detected in liquid products. Database of inorganic and organic N/S/Cl pollutants with larger molecules was established. Organic N/S/Cl functionalities in oily sludge contributed to the majority of N/S/Cl pollutants. NH3, HCN, HNCO, NO, NO2, CS2, SO2, CH3 SH, HCl, and Cl2 were generated between 200 and 600 °C during pyrolysis process, which were much lower than the quantity of corresponding products from combustion. Oxygen-enriched atmosphere in combustion facilitated decomposition of organic fractions, and shifted release regions towards lower temperatures. The decomposition of amine-N functionality contributed to NH3 release below 200 °C. With temperature increasing, heterocyclic-N began to decompose and release abundant NH3, small amounts of HCN and HNCO. Aliphatic-S and disulfides-S contributed to the formation of H2 S, COS, and CS2 .